Penerapan Metode REST API Untuk Presensi Siswa Magang Pada PT. Menara Indonesia - Muhammad Wizli Pratama; Titin Fatimah; Achmad Aditya Ashadul Ushud (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2022)
The development of computer and telecommunications technology at this time has progressed very rapidly and has become a necessity in the scope of individuals and organizations. The presence process is one of the most important things in an agency's scope, especially in agencies that have a high interest in attendance. One of them is an institution that is engaged in the education center. Where student attendance is very important to be recorded in order to be reviewed at a certain period and determine the considerations according to the interests of the agency. Attendance records are usually in the form of signed paper, ID card machines, biometric machines and fingerprints. Over time, the weaknesses that occur from these attendance tools are found, such as queues that can disrupt the attendance process which affects time, fraudulent attendance that is easily manipulated, and documents that can be lost. This study aims to create a presence application using the REST API method. This study uses geolocation technology for the position of the presence location and geocoding to change the coordinates into addresses. Based on the results of web service testing, website and mobile applications can run well as expected, making it easier to collect data related to attendance in order to minimize attendance file loss, fraud and queues during attendance. Using the firebase token as authentication can make the application more secure because the application cannot be accessed if it does not use a token.